PEMAHAMAN PENGGUNAAN TANDA BACA SESUAI DENGAN EJAAN YANG DISEMPURNAKAN (EYD) PADA MAHASISWA JURUSAN AKUNTANSI KELAS A 2012 FE UNIMED – MINI RISET - HALIMATUSSAKDIAH .; BANIA PUTRI (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2014)
"> The objective of this research is to perceive the extent of students’ understanding about the usage of punctuation mark based on Ejaan Yang Disempurnakan(EYD). The research was held at Economy Faculty of UNIMED particularly at Accounting A class of 2012 with 34 students as the population and 20 students as random-choosing sample. The technique of data gathering was by asking the sample to answer an understanding test which containing 10 questions about puctuation mark concept which was covered by sentences. The method of the research is qualitative descriptive. The research result described only 25% of the sample which completely understand of the punctuation mark based on Ejaan Yang Disempurnakan(EYD), whereas 10% of the sample which understand, 20% of the sample which quite understand, and the highest percentage - 45%- is taken by the sample which lack of understanding of punctuation mark. We canconclude that the students are lack of understanding about the usage of punctuation mark based on Ejaan Yang Disempurnakan(EYD). It is possibly caused by interruption at teaching-learning activity or lack of practice to sharpen the understanding after teaching-learning activity. It is expected that the interruption which possibly arise couldbe reduced andfor the students to keep learning and improve the understanding about punctuation mark because it would assist the readers to comprehend the meaning that writers try to deliver.Keywords: Punctuation mark, EYD, Accounting A class.